Gratitude: Building Bridges between Buddhism andPositive Psychology - KHAN, KHATIB AHMAD; YANSHENG, WU; AIGERIM, DANABEKOVA (The journal of contemporary issues in business and government, 2021)
Gratitude is considered as a feeling of appreciation a person receives whether material or immaterial. With gratitude, people acknowledge the goodness in their lives which can also be cultivated by continuous practice. Moreover, The teachings of Buddhism considers gratitude as an spiritual practice to attain the ultimate purpose of life. The field of positive psychology and Buddhism share a common belief on nurturing constructive emotions, personal strengths and virtues. The psychological studies on Buddhism have gradually shown an interest in the area of gratitude and related dimensions in the light of Buddhist teachings. Therefore, present paper draws on centuries of Buddhist teachings and the relevant research done in the area of positive psychology to explore the nature of gratitude and its benefits in everyday life.